The epic of Gilgamesh an English version with an introduction - Sandars, N. K. (Nancy K.) (London, England Penguin Group, 1972)
Presents an English version of the epic poem which dates from the third millenium B.C., telling of the adventures of Gilgamesh, the great king of Uruk, and his search for immortality.
Introduction. 1. The history of the epic -- 2. The discovery of the tablets -- 3. The historical background -- 4. The literary background -- 5. The hero of epic -- 6. The principal gods of the epic -- 7.The story -- 8. Survival -- 9. The diction of the epic -- 10. Remarks on this version -- The Epic of Gilgamesh. 1. The coming of Enkidu -- The forest journey -- Ishtar and Gilgamesh, and the death of Enkidu -- The search for everlasting life -- The story of the flood -- The return -- The death of Gilgamesh.
Includes bibliographical references (pages 126-[128])
Keywords: Epic poetry, Assyro-Babylonian -- Translations into English